Self-powered ultraviolet dual-band photoelectric detector and preparation method thereof

By combining Cs3BiCl6 material with GaN material, the built-in electric field on the interface is used to achieve separation and transmission of photogenerated carriers, the problem of preparation of ultraviolet dual-band photodetectors in the prior art is solved, and a high-performance and low-power self-powered ultraviolet dual-band photodetector is realized.

CN119545969APending Publication Date: 2025-02-28ZHENGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311058129.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively realize the preparation of UV dual-band photodetectors, especially in terms of simplifying processes, improving performance and reducing power consumption.

Method used

The Cs3BiCl6 material is combined with GaN material, and the ultraviolet light absorption capacity of Cs3BiCl6 and the absorption cut-off edge of GaN are used to effectively separate and transmit photogenerated carriers under zero bias voltage, and a self-powered ultraviolet dual-band photodetector without filter is prepared.

Benefits of technology

Effective detection of light on the 200–250 nanometer and 330–350 nanometer bands is achieved, simplifying the process flow, improving device performance, and reducing power consumption, avoiding the complexity and insufficient performance problems in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119545969A_ABST
    Figure CN119545969A_ABST
Patent Text Reader

Abstract

The invention provides a self-powered ultraviolet dual-band photoelectric detector and a preparation method thereof. A Cs3BiCl6 layer is deposited on a GaN layer, GaN and the Cs3BiCl6 layer form a heterojunction, a second contact electrode is deposited on the GaN layer which is not covered by the Cs3BiCl6 layer, and a first contact electrode is deposited on the Cs3BiCl6 layer. According to the invention, rich surface defect state composite photon-generated carriers of the Cs3BiCl6 layer are utilized to realize filtering of light in wave bands of 200-250 nanometers and 330-350 nanometers, and the Cs3BiCl6 layer is combined with GaN of which the absorption cut-off edge is 375 nanometers, so that dual-wave band light detection of 250-330 nanometers and 350-375 nanometers is realized; by means of a built-in electric field constructed by Cs3BiCl6 and GaN, rapid separation and transmission of photon-generated carriers under zero bias voltage are achieved, and therefore the high-performance self-powered ultraviolet dual-band photoelectric detector without the optical filter is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor optoelectronic devices, and in particular relates to a self-powered ultraviolet dual-band photoelectric detector and a preparation method thereof. Background Art

[0002] Dual-band photodetectors have broad application prospects in many fields such as encrypted optical communications, logic circuits, missile warning and guided missiles. At present, there are several methods to achieve dual-band photodetection: 1) connect two single-band photodetectors in parallel, but this will increase the complexity of the process; 2) use alloy materials as the photoactive layer, but alloy materials are prone to phase separation; 3) prepare superlattice and multi-quantum well structures, but it is necessary to control strain and overcome the lattice mismatch between semiconductor layers during epitaxial growth; 4) use materials with dual-band light absorption ability as the photoactive layer, but this method can only prepare photoconductive photodetectors, and the device response speed is slow; 5) combine two materials with different absorption characteristics to achieve dual-band light response. This method is simple to operate and can improve the performance of the device by constructing a heterojunction. The reported dual-band photodetectors are mainly ultraviolet / visible (Y. Zhang, W. Xu, X. Xu, J. Cai, W. Yang, and X. Fang, J. Phys. Chem. Lett. 10, 836 (2019)), visible / infrared (W. Kim, H. Kim, T. Yoo, J. Lee, J. Jo, B. Lee, A. Sasikala, G. Jung, and Y. Pak, Nat. Commun. 13, 720 (2022)) and ultraviolet / infrared (CN 112002781A) dual-band photodetectors, and there are few reports on ultraviolet / ultraviolet dual-band photodetectors. The ultraviolet dual-band photodetector with great development potential is almost unaffected by various electromagnetic interferences, and has the advantages of high anti-interference, strong concealment, low eavesdropping rate, etc. Therefore, it is very important to develop an ultraviolet dual-band photodetector.

[0003] Perovskite is an ideal candidate material for preparing ultraviolet dual-band photodetectors due to its advantages such as adjustable band gap, high absorption coefficient and good carrier mobility. The inorganic lead-free perovskite derivative Cs3BiCl6 has great development potential in large-scale industrial applications because it overcomes the lead toxicity and instability of organic cations in traditional organic-inorganic hybrid perovskites. In addition, Cs3BiCl6 has inherent ultraviolet dual-band absorption characteristics, which provides potential application prospects for ultraviolet dual-band photodetectors. However, only Cs3BiCl6 nanocrystals and Cs3BiCl6 single crystals have been successfully prepared. This is mainly because the solubility of CsCl materials in organic solvents is low, so it is difficult to prepare dense Cs3BiCl6 films using the commonly used spin coating or scraping method.

[0004] In addition, although Cs3BiCl6 thin film has a high dual-band absorption coefficient, the transient fluorescence lifetime of the nanosecond level results in a short carrier diffusion length, which makes it impossible for photogenerated carriers to be effectively collected by electrodes on both sides. Therefore, there is currently no report on photoconductive Cs3BiCl6 thin film-based photodetectors. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the above-mentioned prior art and propose a self-powered ultraviolet dual-band photodetector and a method for preparing the same. The invention utilizes the strong ultraviolet light absorption ability of Cs3BiCl6 material in the 200-250 nanometer and 330-350 nanometer bands, the strong surface defect state recombination of photogenerated carriers on the surface of Cs3BiCl6, the absorption cutoff edge of GaN material at 375 nanometers, and the built-in electric field generated at the Cs3BiCl6 / GaN interface to achieve effective separation and transmission of photogenerated carriers under zero bias, and prepare a filter-free self-powered ultraviolet dual-band photodetector. Its successful preparation will provide new solutions for dual-band photodetectors in terms of simplifying processes, improving performance, and reducing power consumption.

[0006] The technical solution of the present invention is implemented in the following manner: a self-powered ultraviolet dual-band photodetector includes a GaN layer, a Cs3BiCl6 layer is provided on the GaN layer, a first contact electrode is provided on the Cs3BiCl6 layer, and a second contact electrode is also provided on the GaN layer.

[0007] The Cs3BiCl6 layer is located on the GaN layer to form a type II heterojunction. A second contact electrode is provided on the GaN layer not covered by the Cs3BiCl6 layer, and a first contact electrode is provided on the Cs3BiCl6 layer. An ohmic contact is formed between the first contact electrode and the Cs3BiCl6 layer, and an ohmic contact is formed between the second contact electrode and the GaN layer.

[0008] Preferably, the Cs3BiCl6 layer is prepared by dual-source vapor phase co-deposition method.

[0009] Preferably, the specific method for preparing the Cs3BiCl6 layer is as follows:

[0010] Under the protection of inert gas, CsCl and BiCl3 powders with a molar ratio of 3:1 were weighed and ground to obtain a mixed powder. The mixed powder was transferred to a tungsten boat in the evaporation chamber, and the GaN layer was placed face down on the substrate above the tungsten boat. The base pressure of the evaporation chamber was less than 9.9×10 -4 Pa;

[0011] During the deposition of the Cs3BiCl6 layer, the temperature of the substrate is 30 to 250 degrees, the rotation speed of the substrate is 3 to 6 revolutions per second, and the evaporation rate is 0.3 to 2 angstroms per second.

[0012] Preferably, after the deposition of the Cs3BiCl6 layer is completed, the Cs3BiCl6 layer is subjected to a post-annealing treatment.

[0013] Preferably, the post-annealing temperature is 30 to 250 degrees, and the annealing time is 0.5 to 2 hours.

[0014] Preferably, the GaN layer is prepared by metal organic vapor deposition, hydride vapor phase epitaxy or molecular beam epitaxy, and has a thickness of 1 to 3.5 microns.

[0015] Preferably, the thickness of the Cs3BiCl6 layer is 70 to 1000 nanometers.

[0016] Preferably, the first contact electrode is an Au contact electrode, which is prepared by a thermal vacuum evaporation method or a magnetron sputtering method, and has a thickness of 40 to 80 nanometers.

[0017] Preferably, the second contact electrode is an In contact electrode, which is prepared by thermal vacuum evaporation, radio frequency magnetron sputtering or pressed indium particles, and has a thickness of 40 nanometers to 1 millimeter.

[0018] A method for preparing a self-powered ultraviolet dual-band photodetector is carried out according to the following steps:

[0019] (1) Cleaning the GaN layer;

[0020] (2) Covering a portion of the GaN layer, and depositing a Cs3BiCl6 layer on another portion of the GaN layer using a dual-source vapor phase co-deposition method;

[0021] (3) preparing a first contact electrode on the Cs3BiCl6 layer by a thermal vacuum evaporation method or a magnetron sputtering method;

[0022] (4) A second contact electrode is prepared on the shielded portion of the GaN layer by using a thermal vacuum evaporation method, a radio frequency magnetron sputtering method or an indium pelletizing method.

[0023] Beneficial effects of the present invention:

[0024] The present invention utilizes the abundant surface defect state composite photogenerated carriers in the Cs3BiCl6 material to achieve "filtering" of light in the 200-250 nanometer and 330-350 nanometer bands, and further combines with GaN with an absorption cutoff edge of 375 nanometers to achieve dual-band light detection of wavelengths of 250-330 nanometers and 350-375 nanometers; on the other hand, with the help of the built-in electric field at the Cs3BiCl6 / GaN interface, photogenerated carriers are quickly separated and transmitted under zero bias, thereby realizing a high-performance filter-free self-powered ultraviolet dual-band photodetector. The device structure design proposed in the present invention avoids the problems of complex process and poor performance of traditional dual-band photodetectors, and is of great significance to simplifying the process, enhancing performance, and reducing power consumption of ultraviolet dual-band photodetectors.

[0025] The present invention adopts a dual-source vapor phase co-deposition method to prepare Cs3BiCl6 thin films, which has obvious advantages in the preparation of Cs3BiCl6 thin films due to the characteristics of no need for solvents, strong controllability, high repeatability, and mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 It is a schematic diagram of the structure of the ultraviolet dual-band photoelectric detector described in the present invention.

[0028] Figure 2 This is a scanning electron microscope photograph of the Cs3BiCl6 layer in Example 1.

[0029] Figure 3 This is the X-ray diffraction spectrum of the Cs3BiCl6 layer in Example 1.

[0030] Figure 4 Spectral response curves of the ultraviolet dual-band photodetector prepared in Examples 1 and 2 under zero bias.

[0031] Figure 5 Absorption spectra of the Cs3BiCl6 layers prepared in Examples 2, 3, 4, 5 and 6.

[0032] Figure 6 : The transmission spectra of the Cs3BiCl6 layers prepared in Examples 2, 3, 4, 5 and 6.

[0033] Figure 7The normalized spectral response curves of the ultraviolet dual-band photodetectors prepared in Examples 2, 3, 4, 5 and 6 under zero bias.

[0034] Numbers in the figure: 1. GaN layer, 2. Cs3BiCl6 layer, 3. Au contact electrode, 4. In contact electrode. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] like Figure 1 As shown, a self-powered ultraviolet dual-band photodetector of the present invention includes a GaN layer 1, a Cs3BiCl6 layer 2 grown on the GaN layer, an Au contact electrode 3 on the Cs3BiCl6 layer 2, and an In contact electrode 4 on the GaN layer.

[0037] The GaN layer 1 is prepared by metal organic vapor phase deposition, hydride vapor phase epitaxy or molecular beam epitaxy, and has a thickness of 1 to 3.5 microns.

[0038] The Cs3BiCl6 layer 2 is prepared by a dual-source vapor phase co-deposition method and has a thickness of 70 to 1000 nanometers.

[0039] The Au contact electrode 3 is prepared by thermal vacuum evaporation or magnetron sputtering, and has a thickness of 40 to 80 nanometers.

[0040] The In contact electrode 4 is prepared by thermal vacuum evaporation, radio frequency magnetron sputtering or pressed indium particles, and has a thickness of 40 nanometers to 1 millimeter.

[0041] In the present invention, a method for preparing a self-powered ultraviolet dual-band photodetector is carried out according to the following steps:

[0042] (1) Cut the GaN layer into small square pieces, determine the length and width of the GaN layer according to the application scenario, and clean the GaN layer 1;

[0043] (2) depositing a Cs3BiCl6 layer 2 on the GaN layer 1 by a dual-source vapor phase co-deposition method, and using a mask to cover part of the GaN layer during the deposition process so that the Cs3BiCl6 layer is deposited only on another part of the GaN layer;

[0044] (3) an Au contact electrode 3 prepared on the Cs3BiCl6 layer 2 by a thermal vacuum evaporation method or a radio frequency magnetron sputtering method;

[0045] (4) An In contact electrode 4 is prepared on the GaN layer 1 on which the Cs3BiCl6 layer 2 is not deposited by using a thermal vacuum evaporation method, a radio frequency magnetron sputtering method or an indium pellet pressing method.

[0046] Preferably, the length and width of the GaN layer in step (1) are 2 to 10 mm.

[0047] Preferably, in step (2), the Cs3BiCl6 layer 2 is prepared by a dual-source vapor phase co-deposition method:

[0048] In a nitrogen-protected glove box, CsCl and BiCl3 powders with a molar ratio of 3:1 were weighed and ground in a mortar for 30 minutes. After grinding, the mixed powder was transferred to a tungsten boat in the evaporation chamber. The GaN layer was placed face down on the substrate above the tungsten boat. The base pressure of the evaporation chamber was less than 9.9×10 -4 Pa; during the deposition of the Cs3BiCl6 layer, the temperature of the substrate is 30 to 250 degrees, the rotation speed of the substrate is 3 to 6 revolutions per second, and the evaporation rate is 0.3 to 2 angstroms per second; the thickness of the Cs3BiCl6 layer is regulated by controlling the molar amounts of CsCl and BiCl3; after deposition, the Cs3BiCl6 film is post-annealed at a temperature of 30 to 250 degrees and for a time of 0.5 to 2 hours.

[0049] Preferably, the preparation method of the Au contact electrode 3 in step (3) is thermal vacuum evaporation.

[0050] Preferably, the preparation method of the In contact electrode 4 in step (4) is an indium pellet pressing method.

[0051] The preparation method and performance of the present invention are described below in conjunction with specific embodiments.

[0052] Example 1

[0053] (1) Cutting the GaN layer 1 into small square pieces and cleaning the GaN layer 1;

[0054] The GaN layer 1 is prepared by hydride vapor phase epitaxy. The growth substrate is double-sided polished Al2O3. First, a 2-micron thick undoped GaN is grown as a transition layer, and then a 1.5-micron thick n-type GaN layer is grown. The GaN layer 1 is cut into rectangular pieces with a length of 3 mm and a width of 5 mm. After that, the GaN layer 1 is cleaned. First, it is scrubbed with diluted detergent powder (Axe brand strong detergent powder) for 1 minute, and then rinsed with tap water; then, it is ultrasonically cleaned with acetone, ethanol and deionized water solution for 10 minutes each; it is dried with high-purity nitrogen and set aside.

[0055] (2) preparing Cs3BiCl6 layer 2 by dual-source vapor phase co-deposition method;

[0056] In a glove box protected by nitrogen gas, 0.1515 g of CsCl (Baolaite brand) and 0.0946 g of BiCl3 powder (Baolaite brand) were weighed with a high-precision electronic balance, and 0.3 mmol of Cs3BiCl6 was prepared. The mixture was carefully poured into a mortar and ground for 30 minutes. After grinding, the mixed powder was transferred to a tungsten boat in the evaporation chamber. The cleaned GaN layer 1 was placed in an ultraviolet ozone cleaning machine for treatment for 30 minutes, and the treated GaN layer 1 was placed face down on the substrate above the tungsten boat. The temperature of the substrate was set to 150 degrees. The mechanical pump was turned on to evaporation the chamber. When the vacuum degree of the chamber was lower than 5 Pa, the molecular pump was turned on to continue evacuation until the vacuum degree of the chamber was lower than 9.9×10 -4 Pa; open the metal baffle, substrate baffle and substrate heating; manually increase the power, and the evaporation rate begins after the power increases to about 32 watts, and further adjust the power to keep the evaporation rate at 1 angstrom per second; set the rotation speed of the substrate to 4 revolutions per second; open the substrate baffle and substrate rotation, and deposit the Cs3BiCl6 film.

[0057] (3) preparing Au contact electrode 3 by thermal vacuum evaporation;

[0058] A mask plate with 1 mm*1 mm square holes is fixed on the Cs3BiCl6 layer 2, and a square Au contact electrode 3 with a thickness of 40 nm is prepared on the Cs3BiCl6 layer 2 by using a thermal vacuum evaporation method.

[0059] (4) preparing the In contact electrode 4 by using the indium pellet pressing method;

[0060] The indium particles are cut into cubes with a side length of 1 mm, and the indium particles are pressed onto the GaN layer 1 on which the Cs3BiCl6 layer 2 is not deposited using tweezers.

[0061] Figure 2 This is a scanning electron microscope photograph of the Cs3BiCl6 film prepared in Example 1. As shown in the figure, the Cs3BiCl6 film prepared by the dual-source vapor phase co-deposition method exhibits a flat and dense morphology. The grain size of the film is about 80 nanometers, with a large number of grain boundaries, which will help to enhance the probability of photogenerated carriers to recombine in surface defect states.

[0062] Figure 3 This is the X-ray diffraction spectrum of the Cs3BiCl6 thin film prepared in Example 1. As shown in the figure, all the characteristic diffraction peaks are consistent with the standard diffraction of Cs3BiCl6 (space group C2 / c, JCPDS no.96.100.4083), indicating that the pure phase Cs3BiCl6 thin film was successfully prepared.

[0063] Embodiment 2:

[0064] The difference between this embodiment and embodiment 1 is that in step (2), after the deposition of the Cs3BiCl6 film is completed, the Cs3BiCl6 film is transferred to a heating table at 150 degrees for post-annealing treatment for 1 hour. The post-annealing treatment can increase the crystal quality of the film and is expected to achieve higher device performance.

[0065] Figure 4 The spectral response curves of the devices prepared in Example 1 and Example 2 under zero bias are shown in the figure. As shown in the figure, after the Cs3BiCl6 film is post-annealed, the response of the prepared device is improved by 430% compared with the device without post-annealing treatment. This is because the Cs3BiCl6 film after post-annealing has better crystallinity and higher mobility, which will reduce the probability of non-radiative recombination of photogenerated carriers in the device, thereby achieving higher response.

[0066] Embodiment 3:

[0067] The difference between this embodiment and embodiment 2 is that: in step (2), in a glove box protected by nitrogen gas, 0.2525 g of CsCl powder and 0.1577 g of BiCl3 powder were weighed respectively using a high-precision electronic balance to prepare 0.5 mmol of Cs3BiCl6, which was carefully poured into a mortar and ground for 30 minutes; other experimental parameters remained unchanged. The thickness of the Cs3BiCl6 film was increased by increasing the molar amount of Cs3BiCl6.

[0068] Embodiment 4:

[0069] The difference between this embodiment and embodiment 2 is that: in step (2), in a glove box protected by nitrogen gas, 0.5050 g of CsCl and 0.3154 g of BiCl3 powder are weighed respectively using a high-precision electronic balance to prepare 1 mmol of Cs3BiCl6 medicine, which is carefully poured into a mortar and ground for 30 minutes; other experimental parameters remain unchanged.

[0070] Embodiment 5:

[0071] The difference between this embodiment and embodiment 2 is that in step (2), 0.7575 g of CsCl and 0.4731 g of BiCl3 powder are weighed respectively using a high-precision electronic balance to prepare 1.5 mmol of Cs3BiCl6 medicine, which is carefully poured into a mortar and ground for 30 minutes; other experimental parameters remain unchanged.

[0072] Embodiment 6:

[0073] The difference between this embodiment and embodiment 2 is that: in step (1), 1.0100 g of CsCl and 0.6308 g of BiCl3 powder are weighed respectively using a high-precision electronic balance to prepare 2 mmol of Cs3BiCl6 medicine, which is carefully poured into a mortar and ground for 30 minutes; other experimental parameters remain unchanged.

[0074] Figure 5 The UV-visible absorption spectra of the Cs3BiCl6 films prepared in Examples 2, 3, 4, 5 and 6 are shown in the figure. As shown in the figure, all Cs3BiCl6 films have two UV absorption bands. The absorption band at 330 nm can be attributed to Bi 3+ The spin bandgap 1S 0 -3P 1 The double split peaks at the higher energy range (209 nm and 223 nm) can be attributed to Bi 3+ 1S 0 -1P 1 The transition, where the splitting is caused by the Jahn-Teller effect. As the molar amount of the formulated Cs3BiCl6 chemical increases, the thickness of the Cs3BiCl6 film increases and the absorbance increases.

[0075] Figure 6 The UV-visible transmission spectra of the Cs3BiCl6 films prepared in Examples 2, 3, 4, 5 and 6 are shown in the figure. As the molar amount of the prepared Cs3BiCl6 drug increases, the left edge of the shorter wavelength band moves from 230 nanometers to 250 nanometers, and the left edge of the longer wavelength band also moves to the longer wavelength. When the molar amount increases to 2 millimoles, the transmittance of light in the 200-250 nanometer and 320-345 nanometer bands is 0, indicating that the light is completely absorbed by the Cs3BiCl6 film.

[0076] Figure 7It is the normalized spectral response curve of the device prepared in Example 2, 3, 4, 5 and 6 under zero bias. As shown in the figure, under zero bias, all devices show ultraviolet dual-band light response of 250-320 nanometers and 355-370 nanometers. When the light of 200-250 nanometers and 320-345 nanometers with high absorption coefficient irradiates the device, according to Lambert-Beer law, the incident light intensity decays exponentially with the penetration depth, and photogenerated carriers are generated in the shallower area of ​​the Cs3BiCl6 surface. However, due to the limited carrier diffusion length and strong surface defect state recombination of the Cs3BiCl6 film prepared by the dual-source vapor phase co-deposition method, these photogenerated carriers are difficult to reach the depletion region formed by the Cs3BiCl6 / GaN heterojunction, and therefore cannot contribute to photocurrent in the external circuit. When the device is irradiated with light of 250-320nm and 355-370nm with low absorption coefficient, photons can penetrate Cs3BiCl6 to reach the depletion region, and the electron-hole pairs generated by the light are quickly separated by the built-in electric field, which can contribute to the photocurrent. It is worth mentioning that although light with a wavelength greater than 370nm can reach the depletion layer, it cannot contribute to the photocurrent because the photon energy is less than the band gap energy of GaN. In addition, as the molar amount of the formulated Cs3BiCl6 drug increases, the left edges of the two response bands move toward the long wavelength direction, and the responsivity at 320nm decreases. When the molar amount increases to 2mmol, the responsivity of the device at 320nm drops to almost 0, achieving a complete ultraviolet dual-band light response. Therefore, the Cs3BiCl6 film in the device can be used as a filter for the 200-250nm and 330-350nm bands, and combined with GaN to achieve ultraviolet dual-band light response in the 250-330nm band and the 250-375nm band.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-powered ultraviolet dual-band photodetector, characterized in that: It comprises a GaN layer, a Cs3BiCl6 layer is arranged on the GaN layer, a first contact electrode is arranged on the Cs3BiCl6 layer, and a second contact electrode is also arranged on the GaN layer.

2. The self-powered ultraviolet dual-band photoelectric detector according to claim 1, characterized in that: The Cs3BiCl6 layer was prepared by dual-source vapor phase co-deposition method.

3. The self-powered ultraviolet dual-band photoelectric detector according to claim 2, characterized in that: The specific method for preparing the Cs3BiCl6 layer is as follows: Under the protection of inert gas, CsCl and BiCl3 powders with a molar ratio of 3:1 were weighed and ground to obtain a mixed powder. The mixed powder was transferred to a tungsten boat in the evaporation chamber, and the GaN layer was placed face down on the substrate above the tungsten boat. The base pressure of the evaporation chamber was less than 9.9×10 -4 Pa; During the deposition of the Cs3BiCl6 layer, the temperature of the substrate is 30 to 250 degrees, the rotation speed of the substrate is 3 to 6 revolutions per second, and the evaporation rate is 0.3 to 2 angstroms per second.

4. The self-powered ultraviolet dual-band photoelectric detector according to claim 3, characterized in that: After the deposition of the Cs3BiCl6 layer is completed, the Cs3BiCl6 layer is subjected to a post-annealing treatment.

5. The self-powered ultraviolet dual-band photoelectric detector according to claim 4, characterized in that: The post-annealing temperature is 30 to 250 degrees, and the annealing time is 0.5 to 2 hours.

6. The self-powered ultraviolet dual-band photoelectric detector according to claim 1, characterized in that: The GaN layer is prepared by metal organic vapor phase deposition method, hydride vapor phase epitaxy method or molecular beam epitaxy method, and its thickness is 1 to 3.5 microns.

7. A self-powered ultraviolet dual-band photoelectric detector according to any one of claims 1 to 5, characterized in that: The thickness of the Cs3BiCl6 layer is 70 to 1000 nanometers.

8. The self-powered ultraviolet dual-band photoelectric detector according to claim 1, characterized in that: The first contact electrode is an Au contact electrode, which is prepared by a thermal vacuum evaporation method or a magnetron sputtering method, and has a thickness of 40 to 80 nanometers.

9. The self-powered ultraviolet dual-band photoelectric detector according to claim 1, characterized in that: The second contact electrode is an In contact electrode, which is prepared by a thermal vacuum evaporation method, a radio frequency magnetron sputtering method or pressed indium particles, and has a thickness of 40 nanometers to 1 millimeter.

10. A method for preparing a self-powered ultraviolet dual-band photodetector, characterized in that: It is done in the following steps: (1) Cleaning the GaN layer; (2) Covering a portion of the GaN layer, and depositing a Cs3BiCl6 layer on another portion of the GaN layer using a dual-source vapor phase co-deposition method; (3) preparing a first contact electrode on the Cs3BiCl6 layer by a thermal vacuum evaporation method or a magnetron sputtering method; (4) A second contact electrode is prepared on the shielded portion of the GaN layer by using a thermal vacuum evaporation method, a radio frequency magnetron sputtering method or an indium pelletizing method.

Citation Information

Patent Citations

  • Silicon-compatible bipolar heterojunction ultraviolet-near infrared dual-band photoelectric detector and preparation method thereof

    CN112002781A